136k views
18 votes
2 tan 30°
II
1 + tan- 300​

1 Answer

9 votes

Question:


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))

Answer:


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= sin(60^(\circ))

Explanation:

Given


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))

Required

Simplify

In trigonometry:


tan(30^(\circ)) = (1)/(√(3))

So, the expression becomes:


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (2 * (1)/(√(3)))/(1 + ((1)/(√(3)))^2)

Simplify the denominator


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (2 * (1)/(√(3)))/(1 + (1)/(3))


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= ((2)/(√(3)))/(1 + (1)/(3))


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= ((2)/(√(3)))/( (3+1)/(3))


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= ((2)/(√(3)))/( (4)/(3))

Express the fraction as:


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (2)/(\sqrt 3) / (4)/(3)


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (2)/(\sqrt 3) * (3)/(4)


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (1)/(\sqrt 3) * (3)/(2)


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (3)/(2\sqrt 3)

Rationalize


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (3)/(2\sqrt 3) * (√(3))/(√(3))


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (3√(3))/(2* 3)


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= (√(3))/(2)

In trigonometry:


sin(60^(\circ)) = (√(3))/(2)

Hence:


(2tan30^(\circ))/(1 + tan^2(30^(\circ)))
= sin(60^(\circ))

User Savin Sharma
by
5.3k points